Transglutaminase 2 regulates endothelial cell calcification via IL-6-mediated autophagy - Liu, Bo; Cai, Zhiyuan; Wang, Yan; Liu, Xinye; Zhang, Bin; Zheng, Qian; Li, Jingye; Li, Cien; Cui, Yuanbo; Lv, Pengju; Yang, Dongwei (Frontiers in Pharmacology, 2024)
Endothelial cell (EC) calcification is an important marker of atherosclerotic calcification. ECs play a critical role not only in atherogenesis but also in intimal calcification, as they have been postulated to serve as a source of osteoprogenitor cells that initiate this process. While the role of transglutaminase 2 (TG2) in cellular differentiation, survival, apoptosis, autophagy, and cell adhesion is well established, the mechanism underlying the TG2-mediated regulation of EC calcification is yet to be fully elucidated. While numerous studies have explored the regulation of autophagy by interleukin (IL)-6 in various cell types, the majority of these investigations have been limited to cancer cells. To gain a better understanding of the pathogenesis of atherosclerotic calcification, we employed human umbilical vein ECs (HUVECs) to establish an EC calcification model. Our findings demonstrated that TG2 promoted calcification in HUVECs, regulated the NF-κB signaling pathway, and induced IL-6 autocrine signaling in ECs, which serves as a downstream signaling molecule of NF-κB. Finally, the results demonstrated that IL-6 activated the JAK2/STAT3 signaling pathway to suppress autophagy in HUVECs, as shown by AZD-1480, a potent JAK2 inhibitor. In addition, IL-6 promoted calcification in HUVECs, which was inhibited after AZD-1480 treatment. Collectively, our results indicated that the TG2/NF-κB-IL-6-JAK2/STAT3 signaling axis mediated the regulation of EC calcification by modulating endothelial autophagy.